Die Auferweckung des Lazarus in den gottesdienstlichen Hymnen der Orthodoxen Kirche - Hofius, Otfried 1937- (2014)
This essay investigates the liturgical hymns of the Orthodox Church referring to the Johannine story of the Raising of Lazarus (Jn. 11:1-44). These hymns are especially sung at the Services of the Saturday before Palm Sunday known as the Saturday of the holy and righteous Lazarus. The relevant hymns are deep theological interpretations of the Johannine story and therefore an important contribution to the history of exegesis of the Gospel according to St John.
Keywords: Auferweckung des Lazarus; Gospel according to St John; History of exegesis of the Fourth Gospel; Orthodox Church; Orthodox liturgical hymns; The Raising of Lazarus